The Importance of Nutritional Nutrition in Productive Cows - Muhammadiso, Abdulazizov (American Journal of Biodiversity, 2026)
This article investigates the significance of adequate nutrition in maintaining reproductive health and improving fertility in productive cows. Special attention is given to the role of protein, energy balance, vitamins, and macro- and microelements in preventing alimentary infertility. Nutritional deficiencies, particularly of calcium, phosphorus, copper, zinc, manganese, cobalt, and vitamin E, are identified as major contributing factors to reproductive disorders such as ovarian dysfunction, persistent corpus luteum, uterine hypotonia, and delayed postpartum recovery. The study highlights that improper feeding practices and unbalanced rations significantly reduce reproductive efficiency and increase economic losses in livestock farming systems. The findings emphasize that optimizing feeding strategies and ensuring balanced mineral and vitamin intake are essential for improving fertility rates and enhancing overall productivity in dairy cattle.